The Impact of Record Keeping On the Financial Performance of Private Health Institutions in Uganda: A Case Study of Kisubi Hospital Entebbe Municipality Wakiso District - Kayesu Sarah (Uganda Christian University, 2024)
The study focused on the impact of record keeping on the financial performance of private health institutions in Wakiso district Entebbe municipality primarily determining the how record keeping impacts the financial performance of kisubi hospital operating with or without record keeping systems. The study was aimed to establish a relationship between record keeping and the financial performance of health institutions. It sought to achieve the following objectives: find out the relationship between financial record keeping and financial performance, assess the effect of financial record keeping on the quality of health service delivery at Kisubi Hospital, and find out factors contributing to poor record keeping and solutions possible remedies. The study seemed significant as portrayed in the findings and the basis for future expounded research. A cross-sectional survey design was adopted for the study. The target population included employees in all departments at Kisubi Hospital and totaled 250. Stratified sampling techniques resulted in a sample size of 154 respondents. Data collection was done through structured questionnaires and reviews of documents, based on both primary and secondary sources. The Pearson correlation and regression analysis were used to test the relationship between record-keeping and financial performance. Descriptive statistics summarized the data. These results show that good financial record-keeping will enhance the performance of private health institutions through promotion of resource management, efficiency in operations, and service delivery. The respondents added that timely and correct records promote better utilization of resources, which eventually leads to an increase in the level of patient satisfaction. However, some challenges that were identified include lack of staff training, highly antiquated technologies, and a lack of appropriate systems, which impede effective record-keeping and, ultimately, financial performance. This study concluded that proper keeping of financial records is crucial for the success of a private health institution. It suggests advanced technology systems in the management of the hospitals, such as EHR, which might help simplify the operations in financial management. Besides this, training and development programs for employees should be conducted regularly so that they will have the required skills to maintain accurate financial records.